The relationships between cholesterol crystals, NLRP3 inflammasome, and coronary atherosclerotic plaque vulnerability in acute coronary syndrome: An optical coherence tomography study - Xue, Chao; Chen, Qizhi; Bian, Ling; Yin, Zhaofang; Xu, Zuojun; Zhang, Huili; Zhang, Qingyong; Zhang, Junfeng; Wang, Changqian; Du, Run; Fan, Li (Frontiers in Cardiovascular Medicine, 2022)
Background Cholesterol crystals (CCs) in lesions are the hallmark of advanced atherosclerotic plaque. Previous studies have demonstrated that CCs could activate NLRP3 inflammasome, which played an important role in atherosclerotic lesion progression. However, the relationship between CCs, NLRP3 inflammasome pathway, and plaque vulnerability in patients with ACS is still not elucidated. Methods Two hundred sixty-nine consecutive acute coronary syndrome (ACS) patients with 269 culprit lesions were included in this study. CCs and other plaque characteristics within the culprit lesion segment were evaluated by optical coherence tomography (OCT) before percutaneous coronary intervention (PCI). The NLRP3 mRNA expression in peripheral blood mononuclear cells (PBMCs) and the serum levels of interleukin (IL)-1β, IL-18, and other biological indices were measured. Results Cholesterol crystals were observed in 105 (39%) patients with 105 culprit lesions. There were no significant differences in baseline clinical characteristics between the patients with CCs (CCs group, n = 105) and the patients without CCs (non-CCs group, n = 164) within the culprit lesion segment except for lipoprotein(a) [Lp(a)]. The CCs group had a higher level of NLRP3 mRNA expression in PBMCs and higher levels of serum cytokine IL-1β and IL-18. OCT showed that the CCs group had longer lesion length, more severe diameter stenosis, and less minimum luminal area (MLA) than the non-CCs group (all p < 0.05). The frequency of thin-cap fibroatheroma (TCFA), thrombus, accumulation of macrophages, plaque rupture, micro-channel, calcification, spotty calcification, and layered plaque was higher in the CCs group than in the non-CCs groups (all p < 0.05). Multivariate logistic analysis revealed that the level of NLRP3 expression (OR = 10.204), IL-1β levels (OR = 3.523), IL-18 levels (OR = 1.006), TCFA (OR = 3.593), layered plaque (OR = 5.287), MLA (OR = 1.475), macrophage accumulation (OR = 2.881), and micro-channel (OR = 3.185) were independently associated with CCs. Conclusion Acute coronary syndrome patients with CCs in culprit lesions had a higher expression of NLRP3, IL-1β, and IL-18, and had more vulnerable plaque characteristics than patients without CCs. CCs might have interacted with NLRP3 inflammasome activation in patients with ACS, which could contribute to plaque vulnerability in culprit lesions.